Leadership in conservation: integrating a conceptual framework, practice, and capacity building - Webb, Seth A., author; Bruyere, Brett, advisor; Teel, Tara, committee member; Walker, Sarah, committee member; Sagas, Ernesto, committee member (Colorado State University. Libraries, 2025)
As the urgency of global biodiversity loss, ecosystem degradation, and climate change intensifies, leadership is increasingly recognized as essential to advancing conservation outcomes—yet it remains underexamined in both research and practice. This dissertation helps address that gap through a three-part, mixed-methods inquiry that expands our understanding of conservation leadership by developing a conceptual framework, testing its application in a real-world species recovery program, and evaluating graduate conservation leadership capacity building outcomes. Chapter 2 presents a framework for conceptualizing leadership in conservation, structured around five leadership domains—stakeholder engagement, vision, trust, individual champion, and excellence in internal attributes—and fifteen associated leadership practices. The framework emerges from a systematic review of 59 peer-reviewed articles across diverse conservation contexts and offers a structured yet flexible tool for researchers, practitioners, and leadership educators. It contributes to a clarified understanding of conservation leadership as comprising skills to motivate, positively interact with and inspire others toward a shared conservation outcome. Chapter 3 applies and tests the framework through a qualitative case study of the Mountain Plover Nest Conservation Program, a private lands species recovery initiative. Using in-depth interviews and deductive thematic analysis, the study reveals how practices such as trust-building, local leadership, and collaborative landowner partnerships and engagement drive program success. The findings confirm the efficacy of the framework domains and leadership practices from Chapter 2 and build on the corresponding domains of stakeholder engagement and individual champion, while offering insights into the value of stakeholder incentives and the benefits of a local versus external champion. Chapter 4 assesses self-reported competencies, and job relevance of leadership practices aligned with the Chapter 2 framework among alumni of a graduate conservation leadership program. Drawing on quantitative survey data and statistical analyses, findings revealed consistently strong competency and relevance ratings for the leadership practices across time since graduation, and job sectors, with only limited variation. Notable differences were found for three leadership practices—adaptability, perseverance, and leading shared goals—among early alumni of the program and those working in public versus other sector settings. The results support the long-term value and applicability of the leadership domains and practices presented in Chapter 2. Collectively, this dissertation advances understanding of conservation leadership by providing evidence of how it is conceptualized, applied, practiced, and cultivated in emerging conservation professionals working in complex, rapidly changing social-ecological systems.
Keywords: conservation leadership; environmental leadership; natural resource leader; conservation skills; collaborative conservation; leadership framework